A more martial Europe? Public opinion, permissive consensus, and EU defence policy. Issue 2 (3rd April 2019) - Schilde, Kaija E.; Anderson, Stephanie B.; Garner, Andrew D.
ABSTRACT: EU defence policy has been extremely popular over the past three decades, averaging around 75% public support. In fact, no other policy domain is as popular and robust as the idea of pooling national sovereignty over defence. However, public support for EU defence has been dismissed as mere "permissive consensus", rather than genuine support. Scholars have often assumed that public opinion towards European integration is passive and shallow, especially over foreign policy issues, where the public has limited understanding of the complexity of issues. Consistent with contemporary findings about the complexity of comparative foreign policy attitudes, the authors contest the permissive consensus logic and demonstrate that European publics have held coherent preferences over the use of force at the European level. The authors conclude that the slow progress of integration in this area is due to the reluctance of elites rather than to the reticence of Europe's citizens.